ANALISIS PENERAPAN PELAYANAN PRIMA TERHADAP KEPUASAN MASYARAKAT (Studi Kasus pada Kantor Kelurahan Nginden Jangkungan, Surabaya) - Moyu, Erut Edwin; Soesiantoro, Adi (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
The Village is the spearhead of service in government agencies, because the public will first come to the Village Office before asking to get service at the District Office or at government offices on it again. Excellent service concept into a concept adopted by all government agencies in the province of East Java because East Java becameÂ  a pilot project excellent service. The purpose of this study to determine the application of excellent service to the satisfaction of the people at the Village Office Nginden Jangkungan Surabaya. This study is a qualitative type of data used is qualitative data and the source is a source of primary data. Data is collected using questionnaires and interviews. Analysis of the data used is qualitative data analysis. The results showed that the conditions of service of excellence at the Village Office Nginden stilts are as follows: Ability to be in good condition, Attitude is in good condition, Attention was in poor condition, Action are in good condition, Appearance in a state sufficiently, and Accoutability are in good condition. Aspects of excellent service which gives effect to the satisfaction of the user community service at the Village Office Nginden stilts are aspects of attitude, action aspect and appearance aspects of service excellence, so the research hypothesis proposed in the previous chapter, which reads "The application of excellent service at the Village Office Nginden stilts Surabaya provide influence on the satisfaction of the user community service "is proven to three aspects, namely attitude, aspects of the action, and aspects of appearance.Keywords: Excellent service, satisfaction, village office